Lieutenant Governors from Upper Huallaga: between national government and rural communitties - Falla Carrillo, Gonzalo Diego (2021)
The main objective of this research is to understand the nature and performance of lieutenant governors as representatives of the national government and local leaders in rural communities in the Upper Huallaga area. The hypothesis of this study is that the process of designation of the lieutenant governors as local political authorities and the nature of their functions generates the conditions for the exercise of the governance tenures to develop according to the needs and priorities of the communities, rather than as representation of the government. A qualitative research methodology was applied through in-depth interviews and analysis of secondary sources. In this way, the meanings that the lieutenant governors give to their experiences as political authorities in rural localities have been analyzed, relating them to the normative and institutional framework, the state density in rural areas, and the context of Upper Huallaga.